2007
DOI: 10.1536/ihj.48.137
|View full text |Cite
|
Sign up to set email alerts
|

Initial and Long-Term Outcomes of Sirolimus-Eluting Stents for Calcified Lesions Compared With Bare-Metal Stents

Abstract: SUMMARYThe aim of this study was to compare the initial and long-term outcomes of sirolimuseluting stents (SES) and bare-metal stents (BMS) in patients with calcified lesions without performing rotational atherectomy.The subjects were 79 consecutive lesions (38 in the SES group and 41 in the BMS group) which were confirmed to have superficially calcified lesions by intravascular ultrasound. In all lesions, the stent was implanted after predilatation with a balloon.The patient characteristics were not different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…In another study, ISR rate was significantly lower and late loss was significantly smaller in the SES group compared to the BMS group when predilatation was successfully performed before stent implantation. 16 These studies suggested that CCL might not be associated with unfavorable early or late outcomes after SES implantation, which is in line with the results of the present study. In contrast, Kawaguchi et al 17 suggested that severe CCL may be associated with a higher MACE rate at 1 year.…”
Section: Discussionsupporting
confidence: 92%
“…In another study, ISR rate was significantly lower and late loss was significantly smaller in the SES group compared to the BMS group when predilatation was successfully performed before stent implantation. 16 These studies suggested that CCL might not be associated with unfavorable early or late outcomes after SES implantation, which is in line with the results of the present study. In contrast, Kawaguchi et al 17 suggested that severe CCL may be associated with a higher MACE rate at 1 year.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the Taxus IV substudy of 126 BMS patients with moderate to severe calcification on fluoroscopy found an incidence of TLR of 11.9% with MACE of 16.8% (11). Finally, in a small series of 41 patients with superficial calcification >60 degrees on IVUS, Seo et al showed a similar high rate of TLR (19.5%) and MACE (24.4%) (12). Our results, obtained from 884 patients with BMS, a sample size greater than all the above three studies combined, showed a similar high rate of repeat revascularization and of death/MI/repeat revascularization (22.4%).…”
Section: Discussionmentioning
confidence: 90%
“…Of 520 potentially relevant articles initially screened, five trials met inclusion criteria and were included in the final meta‐analysis consisting of a total of 2440 patients (1230 in the DES group, 1210 in the BMS group). One study was a randomised controlled trial (RCT) (247 participants), two studies had a prospective design (1598 participants) and two studies had a retrospective design (595 participants) . Paclitaxel‐eluting stents (PES) and sirolimus‐eluting stents (SES) were solely used in two studies respectively .…”
Section: Resultsmentioning
confidence: 99%